Is Environmental Management Accounting a Discipline? A Bibliometric Literature Review - Handayani, Rahmi; Wirmie Eka Putra; Afrizal (JURNAL ECONOMINA, 2024)
The purpose of this paper is to investigate the body of literature on environmental management accounting (EMA) and provides a quantitative overview of the academic as well as the professional literature constituting the field. By doing so, the paper discusses whether EMA has developed as a discipline. Design/methodology/approach. Based on a database containing 814 (396 of them published in academic journals) publications in English, German and French with a publication date prior to 2012 a bibliometric analysis is conducted. Data on the publications, journals, authors and citations were collected, double-checked and examined by applying bibliometric measures. Findings The bibliometric analysis identifies trends in EMA research publications which show that EMA has developed as a young discipline, but is still faces challenges to get better established in mainstream accounting and management research. Although the publication number is growing, a substantial part of the publications have been published outside mainstream accounting journals in non-accounting journals, books and reports. A recent trend towards establishing specialised environmental (and sustainability) accounting journals is also rendered apparent. The low number of highly cited publications of few authors, however, indicates that EMA is still to become a mainstream field of research. Originality/value The paper discusses with the help of bibliometric analysis and measures whether EMA has developed as a discipline and whether it has become part of mainstream accounting research.